2017
DOI: 10.1074/jbc.m116.758367
|View full text |Cite
|
Sign up to set email alerts
|

RFT1 Protein Affects Glycosylphosphatidylinositol (GPI) Anchor Glycosylation

Abstract: The membrane protein RFT1 is essential for normal protein N-glycosylation, but its precise function is not known. RFT1 was originally proposed to translocate the glycolipid ManGlcNAc-PP-dolichol (needed to synthesize N-glycan precursors) across the endoplasmic reticulum membrane, but subsequent studies showed that it does not play a direct role in transport. In contrast to the situation in yeast, RFT1 is not essential for growth of the parasitic protozoan Trypanosoma brucei, enabling the study of its function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…We observed shared interactors between OC43 and SARS-CoV-2, such as the N -glycosylation factor RFT1 39 , 40 and a sarcoplasmic/endoplasmic reticulum calcium ATPase (SERCA – ATP2A2) 41 . In addition, we identified shared interactors between OC43 and SARS-CoV-1, including a regulator of UPR-mediated apoptosis (WLS or GPR177) 42 , a member of the signal peptidase complex (SEC11A) 43 , and factors involved in cholesterol synthesis (IDI1, DHCR7) 44 47 .…”
Section: Resultsmentioning
confidence: 88%
“…We observed shared interactors between OC43 and SARS-CoV-2, such as the N -glycosylation factor RFT1 39 , 40 and a sarcoplasmic/endoplasmic reticulum calcium ATPase (SERCA – ATP2A2) 41 . In addition, we identified shared interactors between OC43 and SARS-CoV-1, including a regulator of UPR-mediated apoptosis (WLS or GPR177) 42 , a member of the signal peptidase complex (SEC11A) 43 , and factors involved in cholesterol synthesis (IDI1, DHCR7) 44 47 .…”
Section: Resultsmentioning
confidence: 88%
“…Procedures were as previously described 17 . Briefly, 5x10 8 cells were cultured for 16 hours in the presence of 40 µCi of [ 3 H]ethanolamine.…”
Section: Metabolic Labeling and Extraction Of [ 3 H]-ethanolamine-labmentioning
confidence: 99%
“…The M5-DLO scramblase is critically important as N-glycosylation cannot occur without it (we therefore also refer to it as the N-glycosylation scramblase). The polytopic ER membrane protein Rft1 was proposed as the M5-DLO scramblase almost two decades ago 12,13 , but subsequent work showed that whereas Rft1 is clearly important for N-glycosylation, it appears to have no direct role in translocating M5-DLO across the ER membrane 6,[14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…they are ATP-independent, and that they are mediated by ER membrane proteins (termed scramblases) with exquisite substrate specificity 8 10 , 16 , 17 . The ER membrane protein Rft1 was proposed as the M5-DLO scramblase almost two decades ago 18 , 19 , but subsequent work showed that whereas Rft1 is clearly important for N -glycosylation, it appears to have no direct role in translocating M5-DLO across the ER membrane 16 , 20 23 . Likewise, the mammalian protein Lec35/MPDU1 appeared to be involved in MPD scrambling, but likely in the role of a 'dolichol chaperone' that may assist in an as yet undefined way in the scrambling process 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%